An Association Between State Laws Limiting Local Control and Community Smoke-Free Indoor Air in the United States - Azagba, Sunday; Ebling, Todd; Korkmaz, Alperen; King Jensen, Jessica; Qeadan, Fares; Hall, Mark (Journal of primary care & community health, 2024)
This study examines the association between state laws limiting local control (preemption laws) and local smoke-free policies. We utilized policy data from the American Nonsmokers’ Rights Foundation. The primary outcome variable is the presence of a “100% smoke-free policy,” across any of 4 indoor settings: workplaces, restaurants, bars, and gaming venues. We employed generalized structural equation modeling to investigate the relationship between state laws pre-empting smoke-free indoor air regulation and local adoption of policies requiring smoke-free air in any public venues, or for specific venues, adjusting for sociodemographic characteristics. Our findings reveal a significant association between state preemption laws and the presence of a local 100% smoke-free indoor policy as of 2023. In states with preemption laws, cities were less likely to have a 100% smoke-free indoor policy at any venue than cities in states without preemption laws (OR = 0.07, 95% CI = 0.05-0.10). When considering specific smoke-free venues, cities in states with preemption laws were less likely to have a 100% smoke-free indoor policy covering workplaces (OR = 0.05, 95% CI = 0.03-0.09), restaurants (OR = 0.04, 95% CI = 0.02-0.07), bars (OR = 0.04, 95% CI = 0.03-0.08), and gaming venues (OR = 0.03, 95% CI = 0.01-0.09) compared to cities in states without preemption laws. Our study suggests that state preemption laws limit local decision-making and the implementation of public health policies focused on tobacco harms.